2017
DOI: 10.18203/issn.2455-4529.intjresdermatol20170362
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic spontaneous urticaria and thyroid autoimmunity: a case control study from a tertiary care centre

Abstract: <p class="abstract"><strong>Background:</strong> The exact etiology of chronic spontaneous urticaria is unknown in the majority of patients. A subset of chronic spontaneous urticaria can be autoimmune and may be associated with thyroid autoimmunity<span lang="EN-IN">.</span></p><p class="abstract"><strong>Methods:</strong> Serum anti thyroid peroxidase (anti-TPO) antibody level and thyroid function tests (TFT) including triiodothyronine (T3), thyroxine (T4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…So, based on our results colchicine did not have any significant effect on anti‐TPO level. Similarly, Mariysth et al 14 showed that although there was a slight increase in abnormal anti‐TPO antibody level and thyroid dysfunction in patients with chronic spontaneous urticaria compared to controls, it was not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
“…So, based on our results colchicine did not have any significant effect on anti‐TPO level. Similarly, Mariysth et al 14 showed that although there was a slight increase in abnormal anti‐TPO antibody level and thyroid dysfunction in patients with chronic spontaneous urticaria compared to controls, it was not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
“…Our results demonstrated that the triiodothyronine levels fell within the normal range for both groups. Similarly, Mariyath et al (2017) [ 11 ] conducted a study on 100 patients with chronic spontaneous urticaria and 50 controls, wherein the levels of serum anti-TPO antibodies, triiodothyronine (T3), tetraiodothyronine (T4), and TSH were estimated. The results showed that 22% of the patients had abnormal T3 and T4 levels, whereas 22% and 12% of the controls had abnormal TSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the control group had an equal percentage of male and female participants. In another study by Mariyath et al (2017), out of 100 chronic urticaria patients, 75 were women and 25 were men, while the control group consisted of 12 men and 38 women [11].…”
Section: Discussionmentioning
confidence: 99%